Civil society contributions to policy innovation in the PR China: environment, social development and international cooperation - Fulda, Andreas (Palgrave Macmillan, 2015)
This book focuses on the question of whether and how civil society may contribute to policy innovation. As the focus of civil society research is often more on the constraints on civil society by the state and less on the agency and effects of civil society organisations the authors provide a fresh and fruitful perspective.